Laparoscopic versus Open Adrenalectomy for Stage I/II Adrenocortical Carcinoma: Meta-Analysis of Outcomes. (1st June 2015) - Sgourakis, George; Lanitis, Sophocles; Kouloura, Andriana; Zaphiriadou, Paraskevi; Karkoulias, Kyriakos; Raptis, Dimitrios; Anagnostara, Athina; Caraliotas, Constantine
ABSTRACT Aim : The aim of the present meta-analysis was to investigate the safety and oncologic efficacy of laparoscopic adrenalectomy for stage I and II adrenocortical carcinoma. The issue of level I evidence is entirely unreturned. Methods: Electronic databases were used to search for articles from 1992 to 2014 in the English language literature. The primary end point of the study was to evaluate the safety of the laparoscopic procedure in terms of complications and the oncologic effectiveness of the procedure comparing the R0 resection, disease free survival and overall survival of patients treated with open adrenalectomy versus laparoscopic adrenalectomy. Results: Differences in postoperative complications and R0 resections did not reach statistical significance between treatment arms. There were not statistical significant differences between treatment arms considering the two-year, three-year, four-year overall survival while five-year overall survival was in favor of open adrenalectomy group. There were not statistical significant differences between treatment arms considering the two-year, three-year, four-year, and five-year disease free survival. Conclusions: It seems that postoperative complications, R0-resection, overall, and disease free survival of stage I/II adrenocortical carcinoma are comparable and independent to the procedure though the five-year survival was in favor of the open group. Further research is likely to have an important impact on our confidence in the estimates of effect and may change the estimates.